The servant leader : how to create a productive organization by serving those being led - Camp, Robert B. (Productivity Press, 2025)
This book details the way servant leaders think and act. It emphasizes the role of humility in the work of great leaders. Servant leaders see it as their job to grow their people and to remove obstacles from their paths. The servant leader looks ahead and sets out a path for the rest of the organization to follow. We see that dynamic occur as Thomas (the book's central character) embraces Total Productive Maintenance, 5S, and later moonshining. A great leader, Thomas doesn't stand in the limelight himself but pushes his people into it.This novel is about the transformation of an organization through the leadership style of a new leader - By introducing the reader to Thomas Harding, the author illustrates the crucial qualities of servant leaders.
Keywords: Servant leadership.; Industrial management.; elektronické knihy; electronic books